2022
DOI: 10.1038/s41467-022-33059-5
|View full text |Cite
|
Sign up to set email alerts
|

Circuit analysis reveals a neural pathway for light avoidance in Drosophila larvae

Abstract: Understanding how neural circuits underlie behaviour is challenging even in the connectome era because it requires a combination of anatomical and functional analyses. This is exemplified in the circuit underlying the light avoidance behaviour displayed by Drosophila melanogaster larvae. While this behaviour is robust and the nervous system relatively simple, the circuit is only partially delineated with some contradictions among studies. Here, we devise trans-Tango MkII, an offshoot of the transsynaptic circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…As shown in Figure S3A, PTTH immunosignal showed a rhythm in the cell bodies; however we found that this rhythm was not dependent on the clock. (This cycling of PTTH staining in the cell bodies may be dependent on photic inputs, similar to the role of PTTH in light avoidance during larval stages (Yamanaka et al, 2013;Sorkac et al, 2022).) By contrast, PTTH immunoreactivity of the axonal terminals onto the PG showed clock-dependent daily rhythmicity.…”
Section: Coupling Between Central and Peripheral Circadian Clocks 10mentioning
confidence: 55%
See 1 more Smart Citation
“…As shown in Figure S3A, PTTH immunosignal showed a rhythm in the cell bodies; however we found that this rhythm was not dependent on the clock. (This cycling of PTTH staining in the cell bodies may be dependent on photic inputs, similar to the role of PTTH in light avoidance during larval stages (Yamanaka et al, 2013;Sorkac et al, 2022).) By contrast, PTTH immunoreactivity of the axonal terminals onto the PG showed clock-dependent daily rhythmicity.…”
Section: Coupling Between Central and Peripheral Circadian Clocks 10mentioning
confidence: 55%
“…To determine which LNv neurons signal to PTTHn and whether this contact includes synaptic transmission, we performed a connectomic analysis by GFP reconstitution across synapses (syb-GRASP) (Macpherson et al, 2015), BAcTrace (Cachero et al, 2020), and trans-Tango MkII (Sorkac et al, 2022), in adult pharate animals. This work was necessary because the PTTHn can no longer be detected starting shortly after eclosion (Liu et al, 2016) and are therefore not included in the available EM-based connectomic datasets that are based on older adult flies (Scheffer et al, 2020).…”
Section: All Pdf-positive Slnv Signal Non-synaptically To the Ptthnmentioning
confidence: 99%
“… 111 In neonatal mice, photoaversion has been further mapped to a specific M1 class of ipRGCs, 112 and a specific photoreceptor pathway for photophobia in Drosophila larvae has been identified, which, due to their projection regions controlling circadian photoentrainment, is likely functionally related to ipRGCs. 113 ipRGCs persist during normal aging but are susceptible to degeneration even in mature adults in AD, PD, glaucoma, and diabetic retinopathy. 114 Our data indicate that ipRGCs are functionally maintained in light aversion in mice up to 12 months old, regardless of whether they are localized to the GCL or are displaced in the INL.…”
Section: Discussionmentioning
confidence: 99%